Flowability improvers and starch resin composites

JP2026166151APending Publication Date: 2026-10-14OJI HLDG CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2025058926
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0007】 本発明によれば、組成物中の熱可塑性樹脂を融解させたときの流動性と、得られる成形品の強度と、を両立できる流動性向上剤及びこれを含む澱粉樹脂複合材を提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026166151000005
    Figure 2026166151000005
  • Figure 2026166151000006
    Figure 2026166151000006
  • Figure 2026166151000007
    Figure 2026166151000007
Patent Text Reader

Abstract

The present invention provides a fluidity enhancer that can achieve both the fluidity of the thermoplastic resin in the composition when it is melted and the strength of the resulting molded product, as well as a starch resin composite material containing the same. [Solution] A fluidity improver containing starch. A starch-resin composite material containing a thermoplastic resin having ester bonds and starch.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present invention relates to a fluidity improver and a starch-resin composite material.

BACKGROUND ART

[0002] Packaging and containers for food and the like are molded articles of a resin composition containing a thermoplastic resin. The molded articles are required to have practically usable strength according to their applications. However, the thermoplastic resin alone has low fluidity, and there is a problem in handleability during kneading and injection molding. Patent Document 1 proposes a resin composition containing a thermoplastic resin and starch. Patent Document 2 proposes a resin composite material containing a synthetic resin, nanosheets, and a starch-based substance as a filler.

PRIOR ART DOCUMENTS

PATENT DOCUMENTS

[0003]

PATENT DOCUMENT 1

PATENT DOCUMENT 2

SUMMARY OF THE INVENTION

PROBLEMS TO BE SOLVED BY THE INVENTION

[0004] However, Patent Document 1 describes that starch alone has poor fluidity during molding, but does not describe that the fluidity of a thermoplastic resin is improved by starch. Similarly, Patent Document 2 also does not describe that the fluidity of a thermoplastic resin is improved by starch.

[0005] An object of the present invention is to provide a fluidity improver that can achieve both fluidity when a thermoplastic resin in a composition is melted and the strength of the obtained molded article, and a starch-resin composite material containing the same.

MEANS FOR SOLVING THE PROBLEMS

[0006] The present invention has the following aspects. [1] A fluidity improver containing starch as an active ingredient. [2] A starch-resin composite material comprising a thermoplastic resin and starch. [3] The starch resin composite material according to [2], wherein the starch is not gelatinized. [4] The starch resin composite material according to [2] or [3], wherein the starch is at least one selected from the group consisting of unprocessed starch and hydrophobized starch. [5] The starch resin composite material according to any one of [2] to [4], wherein the thermoplastic resin has ester bonds. [6] The starch resin composite material according to any one of [2] to [5], wherein the starch content is 1 to 15% by mass with respect to the total mass of the starch resin composite material. [7] A starch-resin composite material according to any one of items [2] to [6], wherein the ratio expressed as [weight-average molecular weight of the thermoplastic resin after mixing with starch] / [weight-average molecular weight of the thermoplastic resin before mixing with starch] is less than 1. [8] The starch resin composite material according to any one of [2] to [7], wherein the thermoplastic resin is a biodegradable plastic. [9] The starch resin composite material according to any one of [2] to [8], wherein the weight-average molecular weight of the thermoplastic resin in the starch resin composite material is 50,000 to 300,000.

[10] The starch resin composite material according to any one of items [2] to [9], wherein a test piece is formed from the starch resin composite material and the tensile stress measured in accordance with JIS K 7161-1:2014 is 15 MPa or more. A molded article obtained by molding a starch resin composite material as described in any one of items

[11] [2] to

[10] .

[12] A method for producing a starch-resin composite material according to any one of [2] to

[10] , comprising mixing the thermoplastic resin and the starch. [Effects of the Invention]

[0007] According to the present invention, it is possible to provide a fluidity improver that can achieve both the fluidity when the thermoplastic resin in the composition is melted and the strength of the resulting molded article, as well as a starch resin composite material containing the same. [Brief explanation of the drawing]

[0008] [Figure 1] This figure shows the relationship between the starch addition rate and MVR in the examples. [Figure 2] This figure shows the relationship between the starch addition rate and tensile stress in the examples. [Figure 3] This figure shows the relationship between the starch addition rate and the weight-average molecular weight in the examples. [Modes for carrying out the invention]

[0009] In this specification, the "~" symbol indicating a numerical range means that the numbers before and after it are included as the lower and upper limits, respectively. The lower and upper limits of the numerical ranges disclosed herein can be combined in any way to create new numerical ranges.

[0010] (Flow improver) The fluidity improver of the present invention contains starch as an active ingredient. The fluidity improver of the present invention is used in mixture with a thermoplastic resin to improve the fluidity of the thermoplastic resin.

[0011] <Starch> The starch may be unprocessed starch or hydrophobic starch, but hydrophobic starch is preferred because it is easier to improve the dispersibility of the starch. Examples of unprocessed starches include corn starch, potato starch, tapioca starch, wheat starch, and rice starch. Hydrophobized starch is starch that has undergone hydrophobic treatment (water-repellent processing). By using hydrophobized starch, the surface of the starch particles becomes hydrophobic (water-repellent), which improves the dispersibility in thermoplastic resins. Examples of the hydrophobization treatment include, but are not limited to, a treatment of mixing a silicone agent with starch, a treatment of bringing starch into contact with an organosilane aqueous solution in the presence of an alkali aluminate or an alkali hydroxide, a treatment of derivatizing starch with silicone or alkenyl, a treatment of reacting starch with an organic acid anhydride such as octenyl succinic anhydride or dodecenyl succinic anhydride, a treatment of copolymerizing starch with a hydrophobic monomer or a hydrophobic unsaturated monomer such as acrylonitrile, a treatment of imparting a hydrophobic group containing a hydrocarbon group to starch through etherification or esterification, and a treatment of converting starch to an alkyl starch succinate. As the material used for the hydrophobization treatment, it is preferable to use a material having an acidic group such as a carboxy group and a sulfo group, or a basic group such as an amino group, since this makes it easier to improve the dispersibility of starch during kneading, and further facilitates the hydrolysis of the thermoplastic resin having an ester bond, making it easier to enhance fluidity. As the starch before being hydrophobized, those listed as unmodified starch can be used. The starch may be used singly or in combination of two or more kinds.

[0012] The average primary particle diameter of the starch is not particularly limited, but is preferably, for example, 1 to 120 μm, more preferably 1 to 70 μm, and still more preferably 2 to 35 μm. When the average primary particle diameter of the starch is not less than the above lower limit, it is easy to prevent the formation of lumps caused by the aggregation of starch to form secondary particles. When the average primary particle diameter of the starch is not more than the above upper limit, the starch is easily dispersed in the thermoplastic resin. The average particle diameter means the particle diameter at an integrated value of 50% in the particle size distribution determined by the laser diffraction / scattering method.

[0013] The content of starch is preferably 80% by mass or more, more preferably 90% by mass or more, and still more preferably 95% by mass or more, based on the total mass of the fluidity improver. When the content of starch is not less than the above lower limit, the starch is easily dispersed in the thermoplastic resin, so that the fluidity is easily improved. The content of starch is calculated with the weight including water adhering to the starch taken as the total weight of the starch.

[0014] The amount of water adhering to the starch (hereinafter also referred to as the water content) is preferably 1 to 30% by mass, more preferably 2 to 20% by mass, and even more preferably 3 to 15% by mass, relative to the total mass of starch including water. When the water content is above the lower limit, it is easier to disperse in the thermoplastic resin, thus improving fluidity. Furthermore, the ester bonds of the thermoplastic resin can be hydrolyzed to an extent that improves fluidity. In addition, when kneading with the thermoplastic resin, it is easier to uniformly disperse starch molecules and water molecules in the thermoplastic resin than when water is added separately, so it is difficult to evaporate the water molecules necessary for hydrolysis. When the water content is below the upper limit, water is less likely to separate in the thermoplastic resin, making it easier to improve dispersibility. Furthermore, the ester bonds of the thermoplastic resin can be hydrolyzed to an extent that does not reduce the strength of the resulting molded product.

[0015] <Optional ingredients> The fluidity improver may, if necessary, further contain any other optional components besides starch. Optional components include, for example, lubricants, defoamers, thickeners, water-retaining agents, and pigments. Optional components may be used individually or in combination of two or more.

[0016] (Starch resin composite material) The starch-resin composite material contains a thermoplastic resin and starch. The starch-resin composite material contains a thermoplastic resin and a flowability improver.

[0017] <Thermoplastic resin> The thermoplastic resin is not particularly limited, but examples include polyolefins such as polyethylene, polypropylene, and ethylene propylene copolymers, polyesters, polyamides, ethylene vinyl acetate copolymers, polyacrylic acid esters, and polymethacrylic acid esters, and other acrylic resins. Among these, thermoplastic resins having ester bonds are preferred because their molecular weight can be moderately reduced through hydrolysis, which further enhances their fluidity. Ester bonds may be present in the main chain or side chains of thermoplastic resins, but it is preferable that they be in the main chain because hydrolysis makes it easier to reduce the molecular weight appropriately. Examples of resins having ester bonds in the main chain include aliphatic polyesters and aromatic polyesters. As the resin having ester bonds, biodegradable plastics are preferred. Examples of biodegradable plastics include biodegradable polyesters, specifically PLA (polylactic acid), PHBH (poly(3-hydroxybutyrate-co-3-hydroxyhexanoate), copolymer of 3-hydroxybutanoic acid and 3-hydroxyhexanoic acid), PHA (polyhydroxyalkanoate), PES (polyethylene succinate), PBS (polybutylene succinate), PBAT (polybutylene adipate terephthalate, copolymer of 1,4-butanediol, adipic acid and terephthalic acid), PBSA (polybutylene succinate adipate, copolymer of 1,4-butanediol, succinic acid and adipic acid), PGA (polyglycolic acid), PETS (polyethylene terephthalate succinate), PA (polyamide), PC (polycarbonate), PU (polyurethane), and PBSu (polybutylene succinate). Among these, PLA, PHBH, PBS, and PBSA are preferred, with PLA and PHBH being more preferred. Thermoplastic resins may be used individually or in combination of two or more types.

[0018] The weight-average molecular weight of the thermoplastic resin before mixing with starch is preferably 100,000 to 650,000, more preferably 120,000 to 300,000, and even more preferably 135,000 to 250,000. If the weight-average molecular weight before mixing with starch is above the lower limit, it is easier to improve the mechanical strength. If the weight-average molecular weight before mixing with starch is below the upper limit, it is easier to improve the fluidity. The weight-average molecular weight of the thermoplastic resin after mixing with starch is preferably 50,000 to 650,000, more preferably 80,000 to 250,000, and even more preferably 100,000 to 230,000. If the weight-average molecular weight after mixing with starch is above the lower limit, it is easier to improve the mechanical strength. If the weight-average molecular weight after mixing with starch is below the upper limit, it is easier to improve the fluidity. The ratio expressed as [weight-average molecular weight of thermoplastic resin after mixing with starch] / [weight-average molecular weight of thermoplastic resin before mixing with starch] is preferably less than 1, more preferably 0.30 to 0.99, and even more preferably 0.5 to 0.95. If the ratio is above the lower limit, it is easier to improve mechanical strength. If the ratio is below the upper limit, it is easier to improve fluidity.

[0019] The thermoplastic resin content is preferably 85-99% by mass, more preferably 87-98% by mass, and even more preferably 90-97% by mass, relative to the total mass of the starch resin composite material. A thermoplastic resin content above the lower limit tends to improve mechanical strength. A thermoplastic resin content below the upper limit tends to improve fluidity. This does not apply when other materials such as pulp are added.

[0020] <Starch> As for starch, the same type as described above can be used.

[0021] The starch content is preferably 1 to 15% by mass, more preferably 2 to 13% by mass, and even more preferably 3 to 10% by mass, relative to the total mass of the starch resin composite material. If the starch content is above the lower limit, it is easily dispersed in the thermoplastic resin, thus improving fluidity. If the starch content is below the upper limit, it is easier to prevent a decrease in fluidity due to excessive starch aggregation in the thermoplastic resin, which reduces dispersibility.

[0022] The content of the fluidity improver is preferably 1 to 15% by mass, more preferably 2 to 13% by mass, and even more preferably 3 to 10% by mass, relative to the total mass of the starch resin composite. If the content of the fluidity improver is above the lower limit, it is easily dispersed in the thermoplastic resin, thus improving fluidity. If the content of the fluidity improver is below the upper limit, it is easier to prevent a decrease in fluidity due to excessive starch aggregation in the thermoplastic resin, which reduces dispersibility.

[0023] <Optional ingredients> The starch-resin composite material may further contain any components other than thermoplastic resin and starch, if necessary. Optional components include, for example, lubricants, defoamers, thickeners, water-retaining agents, and pigments. Optional components may be used individually or in combination of two or more.

[0024] Examples of lubricants include metal soaps, with metal stearate being preferred and calcium stearate being more preferred. The lubricant content is preferably 0.1 to 5% by mass, more preferably 0.5 to 4% by mass, and even more preferably 1 to 3% by mass, relative to the total mass of the starch resin composite material. If the lubricant content is above the lower limit, injection molding becomes easier and the molded product becomes easier to remove from the mold. If the lubricant content is below the upper limit, it becomes easier to prevent lubricant from bleeding out of the molded product.

[0025] The melt volume rate (hereinafter also referred to as MVR), measured in accordance with JIS K 7210-1:2014, is 4 cm 3 / 10 min or longer is preferable, 4-500 cm 3 10 min is more preferable, 4-300 cm 3 A value of 10 min is even more preferable. If the MVR is above the lower limit, the fluidity will not be too low, resulting in excellent handling during molding. If the MVR is below the upper limit, the fluidity will not be too high, resulting in excellent handling during molding. The corresponding international standard for JIS K 7210-1:2014 is ISO 1133-1:2011.

[0026] The ratio expressed as [MVR measured in accordance with JIS K 7210-1:2014 for starch resin composites] / [MVR measured in accordance with JIS K 7210-1:2014 for thermoplastic resins only] is preferably greater than 1, more preferably 1.2 or greater, and even more preferably 3.0 or greater. When the ratio is above the lower limit, the effect of improving the fluidity of the thermoplastic resin by adding starch becomes easier to achieve.

[0027] When starch resin composites are molded into articles, the tensile stress measured using a dumbbell test specimen in a tensile test according to JIS K 7161 is preferably 15 MPa or higher, more preferably 15 to 100 MPa, and even more preferably 20 to 70 MPa. If the tensile stress is above the lower limit, it is easier to obtain molded articles with high mechanical strength. If the tensile stress is below the upper limit, it is easier to obtain molded articles that are easy to process.

[0028] The ratio expressed as [tensile stress measured using a dumbbell test specimen in a tensile test according to JIS K 7161 for molded articles made from starch resin composites] / [tensile stress measured using a dumbbell test specimen in a tensile test according to JIS K 7161 for molded articles made solely from thermoplastic resins] is preferably 0.7 to 1.2, more preferably 0.8 to 1.1, and even more preferably 0.9 to 1.0. If the ratio is above the lower limit, it is easier to obtain molded articles with high mechanical strength. If the ratio is below the upper limit, it is easier to obtain molded articles that are easy to process.

[0029] (Method of manufacturing starch resin composite material) The method for producing the starch resin composite material of the present invention includes, for example, mixing a thermoplastic resin with starch. One method of mixing is kneading using a kneader. The heating temperature should be within a range where the resin softens and can be kneaded. When thermoplastic resin and starch are kneaded together, the temperature rises due to frictional heat. Therefore, the time to finish kneading is preferably 2 to 15 minutes after the temperature rise due to frictional heat has stopped and the resin temperature has stabilized at ±1°C, more preferably 3 to 10 minutes, and even more preferably 4 to 6 minutes. Examples of kneaders include pressurized kneaders (product name: TDRV3-10GB-E type, manufactured by Moriyama Co., Ltd.).

[0030] <Molded products> The molded article of the present invention is formed from the starch resin composite material of the present invention. Methods for forming molded products include, for example, melting a starch resin composite material and molding it by injection molding. The shape of the molded product is not particularly limited; for example, it may be dumbbell-shaped or sheet-shaped. The sheet thickness is preferably 0.01 to 10 mm, more preferably 0.02 to 7 mm, and even more preferably 0.03 to 5 mm. Examples of injection molding machines include the injection molding machine (product name: J80ADS-60U, manufactured by Nippon Steel Corporation).

[0031] <Application> The molded product of the present invention may be used as a packaging material as is, or it may be used as a packaging material after some processing has been done to the sheet, or it may be molded into a container. Known processing methods can be applied as processing. Examples of applications for the molded product of the present invention include bags such as gusseted bags, single-opening bags, flat bags, and square-bottom bags, as well as various other containers.

[0032] The molded articles of the present invention are preferably biodegradable, and for example, they are preferably biodegradable to the levels of certification A to C in the biodegradable resin certification conducted by TUV AUSTRIA. Specifically, the requirements for certification A include a standard that, when measured in accordance with ISO 14855 (JIS K 6953), "the degree of biodegradation reaches 90% or more within 6 months under an aerobic composting environment at 58°C." The requirements for certification B include a standard that, when measured in accordance with ISO 14855 (JIS K 6953), "the degree of biodegradation reaches 90% or more within 12 months under a composting environment at 28°C." The requirements for certification C include a standard that, when measured in accordance with ISO 17556, "the degree of biodegradation reaches 90% or more within 2 years in soil under a composting environment at 25°C." [Examples]

[0033] The present invention will be specifically described below with reference to examples, but the present invention is not limited to the following description. "Parts" and "%" refer to "parts by mass" and "% by mass," respectively.

[0034] The following ingredients were used. <Thermoplastic resin> PHBH: Poly(3-hydroxybutyrate-co-3-hydroxyhexanoate), a copolymer of 3-hydroxybutanoic acid and 3-hydroxyhexanoic acid (trade name: BP330-10C, manufactured by Bluepha, weight-average molecular weight before mixing with starch: 216,000). • PLA: Polylactic acid (product name: Ingeo 2003D, manufactured by Nature Works, weight-average molecular weight before mixing with starch: 242,000). • PBS: Polybutylene succinate (product name: FZ71, manufactured by Mitsubishi Chemical Corporation, weight-average molecular weight before mixing with starch: 136,000). • PBSA: Polybutylene succinate adipate, a copolymer of 1,4-butanediol, succinic acid, and adipic acid (trade name: FD92, manufactured by Mitsubishi Chemical Corporation, weight-average molecular weight before mixing with starch: 188,000). • PP: Polypropylene (Product name: PM472W, manufactured by Sun Allomer Co., Ltd., weight-average molecular weight before mixing with starch: 620,000).

[0035] <Starch> • Hydrophobized starch (starch that has been hydrophobized, product name: Nonblock S, manufactured by Oji Cornstarch Co., Ltd.). • Unprocessed starch (corn starch, not hydrophobized, product name: Corn Starch, manufactured by Oji Corn Starch Co., Ltd.).

[0036] <Optional ingredients> Lubricant: Calcium stearate, product name: Calcium Stearate G, manufactured by NOF Corporation.

[0037] The following evaluation method was used. <Liquidity> MVR Measurements were taken in accordance with JIS K 7210-1:2014. Specifically, a melt flow rate tester (melt indexer) was used, and the measurement temperature was set to the temperatures listed in Tables 1 to 4, in accordance with JIS K 7210-1:2014 Method B.

[0038] <Tensile stress> Measurements were taken in accordance with JIS K 7161-1:2014.

[0039] <Number average molecular weight (Mn)> The values ​​measured by gel permeation chromatography were converted to polystyrene equivalents. Specifically, the measurements were performed using a high-performance liquid chromatograph (product name: KP-22-13S Dual Pump, manufactured by Fromm (main unit)) and a column (product name: 2xPLgel5μMIXED-C 7.5x300mm, manufactured by Agilent Technologies). However, PP was measured using a high-temperature GPC ("Product name: GPC-IR(registered trademark) type high-temperature gel permeation chromatograph, manufactured by Polymer Char (main unit)" and "Product name: IR6 type MCT infrared detector, manufactured by Polymer Char (detector)") with a column (Product name: 2x TSKgel GMH6-HT+2xTSKgel GMH6-HTL 7.5x300mm, manufactured by Tosoh Corporation).

[0040] <Weight average molecular weight (Mw)> The values ​​measured by gel permeation chromatography were converted to polystyrene equivalents. Specifically, the measurements were performed using a high-performance liquid chromatograph (product name: KP-22-13S Dual Pump, manufactured by Fromm (main unit)) and a column (product name: 2xPLgel5μMIXED-C 7.5x300mm, manufactured by Agilent Technologies). However, PP was measured using a high-temperature GPC ("Product name: GPC-IR(registered trademark) type high-temperature gel permeation chromatograph, manufactured by Polymer Char (main unit)" and "Product name: IR6 type MCT infrared detector, manufactured by Polymer Char (detector)") with a column (Product name: 2x TSKgel GMH6-HT+2xTSKgel GMH6-HTL 7.5x300mm, manufactured by Tosoh Corporation).

[0041] <Dispersion degree (Mw / Mn)> It was determined from the weight-average molecular weight and the number-average molecular weight.

[0042] (Example 1) <Manufacturing of starch resin composite materials and molded products> PHBH as a thermoplastic resin was mixed with 96% by mass of calcium stearate as a lubricant in a pressurized kneader (product name: TDRV3-10GB-E type, manufactured by Moriyama Co., Ltd.). After softening the resin with PHBH at 148°C ± 2°C, 2% by mass of hydrophobic starch was added, and the mixture was kneaded for 5 minutes after the temperature rise due to frictional heat stabilized to obtain a starch-resin composite material. The temperature of the starch-resin composite material at the end of kneading was 152°C. The obtained starch-resin composite material was allowed to cool and then pulverized. Subsequently, dumbbell test pieces were made using an injection molding machine (product name: J80ADS-60U, manufactured by Nippon Steel Corporation), and molded products were obtained.

[0043] (Examples 2-18, Comparative Examples 1-6) Starch resin composites and sheets were obtained in the same manner as in Example 1, except that the composition and manufacturing conditions were changed as described in Tables 1-4. The resins were heated at 160°C±2°C for PLA, 120°C±2°C for PBS, 100°C±2°C for PBSA, and 160°C±2°C for PP.

[0044] The evaluation results for each molded product are shown in Tables 1-4 and Figures 1-3.

[0045] [Table 1]

[0046] [Table 2]

[0047] [Table 3]

[0048] [Table 4]

[0049] In Examples 1-18, it was found that fluidity was improved and tensile stress could be maintained within a practical range compared to Comparative Examples 1-5, in which no starch was added. In Comparative Example 2, the lubricant bled out from the resulting starch resin composite material and could not be used for evaluation. In Examples 17 and 18, where polypropylene without ester bonds was used as the thermoplastic resin, the fluidity was slightly improved compared to Comparative Example 6, in which no starch was added, indicating that starch itself has a fluidity-improving effect. [Industrial applicability]

[0050] According to the present invention, it is possible to provide a fluidity improver that can achieve both the fluidity when the thermoplastic resin in the composition is melted and the strength of the resulting molded article, as well as a starch resin composite material containing the same.

Claims

1. A fluidity improver containing starch as an active ingredient.

2. A starch-resin composite material containing a thermoplastic resin and starch.

3. The starch resin composite material according to claim 2, wherein the starch is not gelatinized.

4. The starch resin composite material according to claim 2, wherein the starch is at least one selected from the group consisting of unprocessed starch and hydrophobized starch.

5. The starch resin composite material according to claim 2, wherein the thermoplastic resin has ester bonds.

6. The starch resin composite material according to claim 2, wherein the starch content is 1 to 15% by mass relative to the total mass of the starch resin composite material.

7. The starch-resin composite material according to claim 2, wherein the ratio expressed as [weight-average molecular weight of the thermoplastic resin after mixing with starch] / [weight-average molecular weight of the thermoplastic resin before mixing with starch] is less than 1.

8. The starch resin composite material according to claim 2, wherein the thermoplastic resin is a biodegradable plastic.

9. The starch resin composite material according to claim 2, wherein the weight-average molecular weight of the thermoplastic resin in the starch resin composite material is 50,000 to 300,000.

10. The starch resin composite material according to claim 2, wherein a test piece is formed from the starch resin composite material and the tensile stress measured in accordance with JIS K 7161-1:2014 is 15 MPa or more.

11. A molded article obtained by molding a starch resin composite material according to any one of claims 2 to 10.

12. A method for producing a starch-resin composite material according to any one of claims 2 to 10, comprising mixing the thermoplastic resin and the starch.

Citation Information

Patent Citations

  • Resin composition and method for producing the same, plasticized starch and method for producing the same

    JP2021127454A

  • Resin Composite Materials

    JP6661820B1